2019
DOI: 10.1103/physrevlett.122.073601
|View full text |Cite
|
Sign up to set email alerts
|

Exciting a Bound State in the Continuum through Multiphoton Scattering Plus Delayed Quantum Feedback

Abstract: Excitation of a bound state in the continuum (BIC) through scattering is problematic since it is by definition uncoupled. Here, we consider a type of dressed BIC and show that it can be excited in a nonlinear system through multi-photon scattering and delayed quantum feedback. The system is a semi-infinite waveguide with linear dispersion coupled to a qubit, in which a single-photon, dressed BIC is known to exist. We show that this BIC can be populated via multi-photon scattering in the non-Markovian regime, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 67 publications
0
105
0
Order By: Relevance
“…In the presence of a lossless waveguide, β = 1, the steady state of the dynamics corresponds to a bound state in the continuum (BIC), as previously discussed in Ref. [26]. It can be shown that the probability of reaching the BIC starting initially in the subradiant state of the atoms is given by | Ψ (t → ∞) |Ψ BIC | 2 = 1/ (1 + η/2) [46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of a lossless waveguide, β = 1, the steady state of the dynamics corresponds to a bound state in the continuum (BIC), as previously discussed in Ref. [26]. It can be shown that the probability of reaching the BIC starting initially in the subradiant state of the atoms is given by | Ψ (t → ∞) |Ψ BIC | 2 = 1/ (1 + η/2) [46].…”
mentioning
confidence: 99%
“…It can have a variety of physical origins such as structured bath spectral densities, strong system-bath couplings, low temperatures, or initial system-bath correlations among others [8,9,[11][12][13][14]. Delay-induced non-Markovian dynamics has been previously studied in the context of the spontaneous emission of single atoms [4,15,[17][18][19][20][21][22][23], bound states in continuum (BIC) of the EM field [24][25][26][27], and entanglement generation in emitters coupled to waveguides [4,28]. The effects of non-Markovianity have also been investigated in collective atomic states in the context of structured reservoirs [29][30][31][32][33] and in the strongcoupling regime [34].…”
mentioning
confidence: 99%
“…1a. Such states correspond to the BICs that have been identified before in one-dimensional systems [20][21][22][23][24][25][26][27][28][29][30][31][32][33], and can be intuitively understood from the interference between the emitted light of the emitter and its afterimage, as schematically depicted in Fig. 1a.…”
mentioning
confidence: 91%
“…As a consequence, the non-Markovianity of the dynamics needs to be taken into account. [37][38][39][40][41][42][43][44][45][46] Various setups to control quantum few-level systems via timedelayed feedback have been studied theoretically and it has been shown that it is possible to control characteristic quantities such as the photon-photon correlation and the concurrence which functions as a measure of entanglement. [47][48][49][50][51][52][53][54][55][56][57][58][59] In these systems, in general, the control parameters that can be used to evoke the desired behavior are the delay time and the characteristic frequency which, depending on the considered setup, can be, for example, the frequency of an involved optical transition or the frequency of a cavity mode.…”
Section: Introductionmentioning
confidence: 99%